Pelatihan Manajemen Seni Pertunjukan kepada Komunitas Seni Kesara - Jefrizal Jefrizal; Ridwan Ridwan; Deni Afriadi (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
The purpose of this training activity is (1) to provide an understanding of the stages of managing a show or event. (2) So that the event can be walk on the planned. To achieve this, training activities are needed including (1) Providing performing arts management materials, (2) Assisting partners and to be holding Komunitas Kesara that will launch a poetry musical album.